Pengolahan Limbah Organik Rumah Tangga Menjadi Kompos Melalui Penerapan Metode Takakura - Wardatul Hidayah; Diepa Febriana Wulandari; Wike Pratiwi (Fakultas Teknik Universitas Palangka Raya, 2023)
Waste-related problems are serious problems that are being faced by the Samarinda City government. Waste production in Samarinda City reaches 500 tonnes/day. The programmes presented by the Department of Environment (DLH) of Samarinda City currently focus on inorganic waste management. In fact, half (50%) of the total waste production in Samarinda City comes from organic waste, especially those generated from household activities. This community service programme aims to provide education to the community, especially the Family Welfare Empowerment (PKK) group on how to process household organic waste so as to produce compost that can be used by the community. The method used in this composting is the Takakura method. The dedication programme for the use of household waste into compost is important to do in order to reduce household waste in the environment and change the perspective regarding waste that has no economic value. This service program has produced products in the form of compost that is dark in colour (blackish-black), fine textured and compost temperatures ranging from 300C-350C. Based on questionnaires and interviews, 75% of participants understood the material presented, 90% had a high level of satisfaction with the programme and 50% of participants stated that they were willing to apply the composting method.